Towards a model for integrative medicine in Swedish primary care - Falkenberg Torkel; Warenmark Anders; Halpin Jeremy; Sundberg Tobias (BMC, 2007)
Abstract Background Collaboration between providers of conventional care and complementary therapies (CTs) has gained in popularity but there is a lack of conceptualised models for delivering such care, i.e. integrative medicine (IM). The aim of this paper is to describe some key findings relevant to the development and implementation of a proposed model for IM adapted to Swedish primary care. Methods Investigative procedures involved research group and key informant meetings with multiple stakeholders including general practitioners, CT providers, medical specialists, primary care administrators and county council representatives. Data collection included meeting notes which were fed back within the research group and used as ongoing working documents. Data analysis was made by immersion/crystallisation and research group consensus. Results were categorised within a public health systems framework of structures, processes and outcomes. Results The outcome was an IM model that aimed for a patient-centered, interdisciplinary, non-hierarchical mix of conventional and complementary medical solutions to individual case management of patients with pain in the lower back and/or neck. The IM model case management adhered to standard clinical practice including active partnership between a gate-keeping general practitioner, collaborating with a team of CT providers in a consensus case conference model of care. CTs with an emerging evidence base included Swedish massage therapy, manual therapy/naprapathy, shiatsu, acupuncture and qigong. Conclusion Despite identified barriers such as no formal recognition of CT professions in Sweden, it was possible to develop a model for IM adapted to Swedish primary care. The IM model calls for testing and refinement in a pragmatic randomised controlled trial to explore its clinical effectiveness.